2021
DOI: 10.1002/ldr.3892
|View full text |Cite
|
Sign up to set email alerts
|

How does land use/cover influence gully head retreat rates? An in‐situ simulation experiment of rainfall and upstream inflow in the gullied loess region, China

Abstract: Land use/cover plays a crucial role in gully head retreat (GHR). However, little is known about how land use/cover influences GHR rates. An in situ simulation experiment of rainfall and upstream inflow was conducted in a gullied loess region to investigate hydraulic erosion, mass movements, and linear GHR processes under three types of land use/cover (bare land, grassland, and shrub-grass land). The results showed that the average linear GHR rates on grassland and shrub-grass land were 87-89% and 72-81% lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…Additionally, its lower part gradually formed an overhang and then gradually lost stability and collapsed. The above collapse process was consistent with the results of (Kang et al, 2021). During the collapse process, another interesting phenomenon was observed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, its lower part gradually formed an overhang and then gradually lost stability and collapsed. The above collapse process was consistent with the results of (Kang et al, 2021). During the collapse process, another interesting phenomenon was observed.…”
Section: Discussionsupporting
confidence: 93%
“…In terms of runoff, the main types of collapse in the BL were divided into two types: headwall collapse and gully bank collapse (Figure 14). Headwall collapse was primarily caused by runoff scouring at the bottom of the headwall, which caused the headwall to overhang and then collapse (Kang et al, 2021). Gully bank collapse was caused by concentrated runoff scouring the bottom of the gully bank, which caused the gully bank to overhang and then collapse.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally found that human activities accelerated gully erosion mainly by destroying vegetation and changing land use (Kang, Wang, et al, 2021; Poesen, 2018; Shellberg, 2021; Wen et al, 2021). But in this research, human activities reduced the gully quantitative characteristics of AF to a certain extent (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Gully development includes headcut retreat, sidewall collapse, and bed downcutting (Harvey, 1992). Gully erosion is affected by many influencing factors, including soil, lithology, climate, topography, vegetation, and human activities (Kang, Wang, et al, 2021; Poesen, 2018; Shellberg, 2021; Wen et al, 2021). As the materials of gully erosion, soil and lithology determine the erodibility (Poesen, 2018; Zhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Torri and Poesen [17] stated the significant effect of land use on the initiation of gully erosion, but Hayas et al [14] and Vandekerckhove et al [18] reported that land use had no or little effect. In fact, the land use / cover was closely related to vegetation traits, so the effect of land use/cover on gully erosion was also dependent on vegetation type, cultivation technics, root traits, and especially the extent and architecture of its root systems [19][20][21]. For example, Guo et al [16] suggested that the roots with diameters of 0-0.5 mm had greater effects on soil loss and morphological evolution of gully headcut erosion than roots with larger diameters.…”
Section: Introductionmentioning
confidence: 99%